The Lark’s Song: A Beckoning to Freedom (SCAFFOLD: A SHOWCASE OF VANDERBILT FIRST-YEAR WRITING, 2022)
A fox, a fig, and a flashlight. What they have to do with one another—no one could tell upon first hearing. A young fox desperate to break free from the doldrum of life as he knows it, endeavors on a life changing journey. A lark’s song illuminates his path, an auspicious messenger. A miraculous flashlight aids him from heavenward. A fig lay set aside as his preeminent destination.For additional context, listen to the author's reflection on the piece below.